Rui Morais. Greek Art from Oxford to Portugal and Back Again: Tribute to Maria Helena Da Rocha-Pereira, with a foreword by Delfim Leão. - Osborne, Robin (Journal of Greek Archaeology, 2018)
This is really a book about the transmission of motifs in ancient art, and essentially consists of a series of examples linked by a very brief and somewhat idiosyncratic text which appears to have had no editing; the penultimate sentence reads ‘The theme of the migration and circulation of images, subject to certain coordinates and the complexities of historical times, manifests in an anachronistic manner, lost in the collective memory’.